Assessing the Suppressive Effects of Organic Amendments From Grapevine Pruning Wood on the Fungus Lasiodiplodia brasiliensis and Their Impact on the Microbiome - Guerrero Cabrera, Luis (2025)
Botryosphaeria dieback, caused by various pathogens, including Lasiodiplodia spp., is a significant threat to grapevines. Lasiodiplodia brasiliensis has been frequently isolated from grapevines in Baja California and Sonora, Mexico, mainly from plants showing perennial cankers. While chemical and biological control strategies have been explored, alternatives such as organic amendments (OAs) have yet to be studied. This research aimed to evaluate the effect of OAs on the co-occurrence of latent L. brasiliensis infection and the grapevine endophytic community using qPCR and metabarcoding analysis. Two OAs, compost cow manure and grapevine wood (CMW) and sludge kitchen waste and grapevine wood (KWW), were tested. Extracts were prepared by mixing 140 g of each OA with 210 mL of autoclaved water, shaking for 2 h, and filtering. Grapevine cuttings were soaked in the extracts for 10 days, then inoculated with a L. brasiliensis MXBCL28 conidiospore suspension (1 × 105 spores mL−1) and incubated for 30 days. Among treatments, cuttings treated with 10% KWW extract exhibited the highest plant growth parameters, including the number and length of lateral shoots, inflorescences, and roots, with a 70% suppressive effect on L. brasiliensis. The KWW treatment also enhanced the abundance of beneficial endophytic genera, including Acinetobacter, Hymenobacter, Pseudomonas, and Flavobacterium, which were significantly associated with antagonistic activity against the pathogen. Meanwhile, genera such as Sphingomonas, Ochrobactrum, Azospirillum, and Rheinheimer appeared to be involved in plant-induced systemic resistance. Furthermore, the dominant bacterial genus DMER64 and fungal genus Orbilia, both present in KWW, were recruited to colonize grapevine tissues, potentially promoting plant growth and physiological processes. Overall, the KWW sludge demonstrated multiple suppressive actions, such as the release of humic substances and biochemical compounds, which facilitate the recruitment of beneficial microorganisms in response to latent L. brasiliensis infection. These findings suggest that KWW is a promising alternative for managing grapevine pruning waste, effectively reducing GTD pathogen transmission while enhancing beneficial endophytic communities.